Vital parameters in Spanish alpine skiers training at altitude and their relationship to human health - Javier Conde-Pipo; Ignacio Valenzuela-Barranco; Rafael Peñafiel; Maria Jose Jimenez-Casquet; Alejandro Lopez-Moro; Miguel Mariscal-Arcas (Archives of Nursing Practice and Care - Peertechz Publications, 2022)
Background: Mediterranean lifestyle has consistently been shown to reduce cardiovascular morbidity and mortality. Physical activity is beneficial to health, although it needs to be carefully studied in extreme conditions. Hypertension depends on sedentary lifestyles, stress, and bad habits such as excessive consumption of food and salt. Chronic sleep deprivation alone has been associated with cardiovascular diseases such as hypertension, diabetes, and obesity. The patient must be educated. Aim: The main objective of this study was to evaluate parameters of non-invasive health such as blood pressure and heart rate in the federated population in winter sports in Andalusia (Spain) relating to body composition. Methods: Cross-sectional observational study. Sample of 234 subjects currently federated in the Andalusian Federation of Winter Sports (Spain). Ages between 12-30yrs (51.6% women, 48.4% men). Subjects carried out surveys with a physical examination, blood pressure measurements, electrocardiogram performance, and parameters to assess body composition. Results: None of the younger male subjects had hypotension or bradycardia (76.6% normotensive, 80.4% normal heart rate). None of the adults had hypotension or tachycardia (82.4% normotensive) and none of the women had bradycardia. Mean weight values (men and women) with a tendency to significance (p = 0.064). %Fat means of men was 19.18% (SD: 5.90) and 23.61% (SD: 8.91) for women. For systolic and diastolic tensions no differences were found by gender. There is no correlation between systolic and diastolic blood pressure with body composition or nutrient intake, however, there is a negative correlation between hours of sleep and blood pressure (p < 0.001). Conclusion: %fat can inform of the risk of cardiovascular diseases. Performing intense aerobic physical exercise can cause sinus bradycardia at rest. Sleeping and having a restful and deep sleep reduces the risk of suffering from high blood pressure. Assessing blood pressure and anthropometric measurements is important to estimate the general health of children, adolescents, and adults. This is the case with alpine skiing in the south of Spain where the athlete lives in these conditions. Future works related to this population living in high-altitude conditions should be studied to see the impact of altitude on the health and sporting performance of acclimatized people.